The demand for military spending in Latin American countries - Christos Kollias; Suzanna-Maria Paleologou; Panayiotis Tzeremes; Nickolaos Tzeremes (Latin American Economic Review, 2018)
The allocation of resources to defence and national security is influenced by several factors, both domestic and external. Empirical findings suggest that military spending is determined by economic, strategic, political, and security factors. Studies that estimate demand functions for such budgetary outlays focus either on individual country case studies or on groups of countries that share some similar traits and characteristics or belong to the same geopolitical region. This paper, using a panel of 12 Latin American countries and quantile regression analysis, estimates the demand for military expenditure over the 1965-2015 period. Results reported herein indicate that such spending has been driven by both domestic and external factors. The former include the economy as well as the political characteristics of the government as these are quantified by the Polity index of democracy. Intrastate conflict that has plagued many Latin American countries also emerges as a strong driving force in the allocation of resources to defence. Military spending by neighbouring countries with common borders emerges as the external strategic determinant that affects the demand for defence expenditures.
Keywords: H56; C21; C23; 330; Latin America; Military spending; Quantile regression